WRITING WITHOUT PERMISSION: A CASE STUDY ON SKINNER’S ANALOGY THROUGH VANDALISM - MANERA, ALMA BANGAYAN (International Journal of Psychosocial Rehabilitation, 2020)
This study is elucidated on the psychological underpinnings of the testimonies and commentaries of the students’ vandals which employed qualitative research. This also disentangled the emotions and opinions thematically made to be used by the student vandals through a case study with a narration. The respondents came from public and private high schools. The study used the purposive sampling and snow ball technique and utilized an in-depth interview in gathering data through narration of academic or social lived experiences. The theory of B. F. Skinner, theory of reinforcement and radical behaviorism was also employed in order assessed the psychological impacts of vandalism. In the narratives of the student vandals, the respondents were deeply affected by their violations. These also revealed that students were motivated and inspired when school authorities give rewards to their actions and outputs, in like manner when they violated and even punished such, students were also dampen and rebellious and so they resort to put in writings their emotions in any surfaces in the school. Vandalism is less prevalent in schools were students feel and experience that they are part of the school, they share in the decision making and ultimately succeed in their academic endeavor .With this acts, school authorities are encourage to give equal activities among students in order to address this kind of problem.